Studing the Influence of Helicobacter.pylori in Celiac Disease Patients - Farah Hamza Mahdee; Shurooq Rayyis Kadhim; Wassan Abdulkareem Abbas (College of Pharmacy / Mustansiriyah University, 2023)
Celiac disease an autoimmune disease; it occurs in Europe at 1%, and in the world people (0.3-1.3%). It causes histopathological changes in the mucosa of the intestine (villi atrophy). The findings showed that it occurs due to the reduction of the absorbed nutrients. Helicobacter pylori are colonized in human gastric mucosa, which mainly causes stomach injury. The rate of H. pylori is as high as almost 50%, and it also occurs in childhood. Vitamin/mineral deficiencies, weight loss, and Malabsorption characterize classical celiac disease. The study aimed to detect the effect of H. pylori in celiac patients and determine vitamin B12, D3, and Ferritin in celiac patients infected with H. pylori. The study includes 41 celiac patients with H. pylori and 31 celiac cases without H. pylori of both genders and 52 apparently healthy individuals of comparable age and gender to save as a control group. The vitamin D3, B12, and ferritin levels were measured for each participant. The study found a positive correlation between celiac and H. pylori, with decreased ferritin levels in patients with celiac disease. Also, the patient group showed a significant decrease in Vitamin D3. Also, the B12 level in the patient group decreased. There was no significant gender-related variation between males and females regarding the patient and control groups' Ferritin, vitamin D3, and Vitamin B12 levels. There was no significant age-related variation between individuals under 35 years of age and those over 35 years of age regarding the ferritin and vitamin B12 levels in the patient and control groups. However, vitamin D3 level was lower in patients less than 35 years of age than in cases with more than 35 years of age. Minerals and vitamin deficiencies are observed in untreated CD cases irrespective of age and gender and irrespective of H. pylori. All CD patients had one or more nutritional deficiencies. Serum nutritional parameters like iron, Vitamin B12, and D3 should be included in the clinical workup of CD patients in addition to the serological markers. It was found that H.pylori does affect the levels of ferritin ,vitamin B12 and vitamin D3 in celiac patients .This study confirmed that there is a positive correlation between H. pylori and celiac disease. In addition, H. pylori infection may aggravate some symptoms of CD.